Associations Between Functioning and PTSD Symptom Clusters in a Dismantling Trial of Cognitive Processing Therapy in Female Interpersonal Violence Survivors. Issue 5 (October 2014) - Shnaider, Philippe; Vorstenbosch, Valerie; Macdonald, Alexandra; Wells, Stephanie Y.; Monson, Candice M.; Resick, Patricia A.
<x xml:space="preserve">Abstract</x> This study conducted secondary analyses of a published trial and sought to determine if different domains of psychosocial functioning (e.g., daily living, work, nonfamily relationships) improved following trauma‐focused treatment for posttraumatic stress disorder (PTSD). Cognitive processing therapy (CPT), an empirically supported treatment that involves evaluating trauma‐related beliefs and written trauma accounts, was compared to its components: CPT without the written accounts or written accounts only in a sample of 78 women with PTSD secondary to interpersonal violence. Overall and individual domains of functioning significantly improved with treatment and results were similar across treatment groups, Fs (2, 150) ≥ 11.87, ps < .001. Additionally, we investigated whether changes in different PTSD symptom clusters were associated with outcomes in domains of psychosocial functioning, after collapsing across treatment condition. Multiple hierarchical linear regression analyses revealed that overall clinician‐assessed PTSD symptom reduction was associated with outcomes in all domains of functioning, βs = .44 to .68, ps < .001. Additionally, improvements in the emotional numbing symptom cluster were associated with outcomes in the nonfamily relationships domain, β = .42, p < .001, and improvements in the hyperarousal symptom cluster were associated with outcomes in the overall, daily living, and household tasks domains, βs = .34 to .39, ps < .01. Results suggest that it may be important to monitor improvements in emotional numbing and hyperarousal symptoms throughout treatment to increase the likelihood of changes in psychosocial functioning.